Pengaruh Partisipasi Anggaran dan Buddget Emphasis Terhadap Budgetary Slack melalui Asimeteri Informasi sebagai Variabel Mediasi pada Dinas Kearsipan dan Perpustakaan Kota Kupang - Putra, Dewa Putu Sumardhika; Manafe, Henny A.; Bibiana, Rere Paulina (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to find out whether there is an effect of budget participation, budget emphasis on budgetary slack through information asymmetry as a mediator at the Kupang City Archives and Library Office. The contribution of this research is expected to contribute to science in the field of regional financial management in order to improve performance in the organization in order to improve service quality. This research is quantitative in nature with the population being all employees of the Kupang City Archives and Library Office and the entire population is sampled. The data collection technique used was a questionnaire with a research tool using Smart PLS 3. The results of the study are that there is a negative and significant influence of budget participation on budgetary slack, budget emphasis is not significant on budgetary slack, information asymmetry has a positive and significant effect on budgetary slack, information asymmetry has a positive effect on budgetary slack, budget participation has a significant effect on information asymmetry, budget emphasis has an insignificant effect on information asymmetry, information asymmetry is able to provide The effect of budget participation on budgetary slack and information asymmetry are unable to mediate the effect of budget emphasis on budgetary slack.